Antihyperon Polarization in Inclusive Processes at High Energies - C. C. Barros (Brazilian Journal of Physics, 2004)
We propose a model that we believe is the main source of the antihyperon polarization in high-energy protonnucleusinclusive reactions. The polarization is originated by the final-state interactions between the antihyperonsand other produced particles in these collisions (predominantly pions). The model is based on two elements:the low-energy pion-hyperon interaction (described by chiral effective Lagrangians) and the statistical fluctuationsplus expansion of the background matter.